2009
DOI: 10.1097/mnm.0b013e32832e0c13
|View full text |Cite
|
Sign up to set email alerts
|

FDG positron emission tomography/computed tomography scan may identify mantle cell lymphoma patients with unusually favorable outcome

Abstract: Staging FDG PET/CT is superior to CT and may be used in the future for identification of a subset of MCL patients with a better outcome than otherwise expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 12 publications
1
30
0
5
Order By: Relevance
“…Other investigators have reported that a higher SUV max at baseline is associated with worse survival [22,23]. In these reports, the cutoff SUV max values that stratified patients into high risk versus low risk groups were 5 and 6, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Other investigators have reported that a higher SUV max at baseline is associated with worse survival [22,23]. In these reports, the cutoff SUV max values that stratified patients into high risk versus low risk groups were 5 and 6, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…En LNH del manto una captación alta se asocia a presencia de blastoides y variante de células grandes, lo que se sabe determina un curso más agresivo de la enfermedad 15 . Karma y cols describen que un SUVmax > 5 se asoció a menor sobrevida en pacientes con LNH del manto (sobrevida a 5 años 34% vs 87% en pacientes con SUVmax ≤ 5) 17 . Entonces, en algunos casos la valoración pronós-tica pretratamiento dependería no sólo de la extensión de la enfermedad, sino también de la avidez de captación de F18-FDG.…”
Section: Discussionunclassified
“…At present, there are very few prospective data to support the use FDG-PET CT for staging, during therapy and after therapy outside of a clinical trial [Brepoels et al 2008;Gill et al 2008aGill et al , 2008b. However, in the context of relatively intensive chemotherapy regimens, FDG-PET CT has shown to have prognostic value, with higher progression-free survival (PFS) and OS rates reported in MCL patients who are FDG-PET-negative at the completion of chemotherapy [Karam et al 2009;Schaffel et al 2009;Mato et al 2012].…”
Section: Discussionmentioning
confidence: 99%